Advantages of Integrating Pressure-Regulating Devices Into Mechanical Circulatory Support Pumps. Issue 1 (January 2019) - Horvath, David J.; Karimov, Jamshid H.; Byram, Nicole A.; Kuban, Barry D.; Sunagawa, Gengo; Moazami, Nader; Fukamachi, Kiyotaka
Abstract : Control of mechanical circulatory support pump output typically requires that pressure-regulating functions be accomplished by active control of the speed or geometry of the device, with feedback from pressure or flow sensors. This article presents a different design approach, with a pressure-regulating device as the core design feature, allowing the essential control function of regulating pressure to be directly programmed into the hydromechanical design. We show the step-by-step transformation of a pressure-regulating device into a continuous-flow total artificial heart that passively balances left and right circulations without the need for pressure and flow sensors. In addition, we discuss a ventricular assist device that prevents backflow in the event of power interruption and also dynamically interacts with residual ventricle function to preserve pulsatility.